2020
DOI: 10.1111/nph.17123
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of date palm (Phoenix dactylifera) seedlings to seawater and flooding

Abstract: • In their natural environment along coast lines, date palms are exposed to seawater inundation and, hence, combined stress by salinity and flooding. • To elucidate the consequences of this combined stress on foliar gas exchange and metabolite abundances in leaves and roots, date palm seedlings were exposed to flooding with seawater and its major constituents under controlled conditions. • Seawater flooding significantly reduced CO 2 assimilation, transpiration and stomatal conductance, but did not affect isop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 78 publications
2
5
0
Order By: Relevance
“…The SOD results showed that the augmentation of NaCl concentrations from 0 g/L to 16 g/L induced an increase in SOD production. Our results are confirmed by numerous other previous works demonstrating the enhancement of SOD expression in plants stressed with salt [61][62][63][64][65].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The SOD results showed that the augmentation of NaCl concentrations from 0 g/L to 16 g/L induced an increase in SOD production. Our results are confirmed by numerous other previous works demonstrating the enhancement of SOD expression in plants stressed with salt [61][62][63][64][65].…”
Section: Discussionsupporting
confidence: 91%
“…Ashraf et al [78] reported that plants biosynthesis of secondary metabolites varies in response to biotic and abiotic conditions. Du et al [64] mentioned that halophytic plants accumulate stress-protective metabolites under saline conditions. The tentatively predicted metabolites belong mostly to the terpenoids, which are known for their activities against plant biotic and abiotic stresses [28,79,80].…”
Section: Discussionmentioning
confidence: 99%
“…ABA is known to accumulate in response to soil drying and salt stress (Karimi et al., 2021), leading to altered expression of thousands of genes and physiological acclimation to stress, such as the closing of stomata (Essah et al., 2003; Finkelstein & Rock, 2002; Kempa et al., 2008; Yoshida et al., 2014). This osmotically driven closure of stomata leads to decreased stomatal conductance, which in turn negatively affects CO 2 assimilation rate in date palm (Du, Ma et al., 2021; Sperling et al., 2014; Yaish et al., 2017). The latter, however, is likely being caused by ABA‐mediated reduction of stomatal conductance (approx.…”
Section: Resultsmentioning
confidence: 99%
“…The halophytic date palm ( Phoenix dactylifera L.) is one of the most important crops in the semi‐ to hyperarid Arabian Peninsula. This is because of its tolerance to adverse environmental conditions such as heat, drought, and salt stress (Al‐Bahrany & Al‐Khayri, 2012; Arab et al., 2016; Du et al., 2021, 2021, 2023). However, there is limited knowledge regarding which of the well‐known strategies for surviving salinity are employed by date palms, and nothing is known about whether these strategies are active in the roots, the shoots, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Date palm tree (Phoenix dactylifera L.) is a diploid plant with 2n = 36 chromosome number, a perennial monocotyledonous plant belonging to the Arecaceae family [1,2]. It is one of the oldest known fruit-bearing tree crops with extensive cultivation and utilization in North Africa and Middle East for at least 5000 years and believed to have originated in Mesopotamia [2][3][4][5]. Date palms have a great socio-economic impact and an eminent contribution in agricultural sustainability in many arid and semiarid parts of the world [1,6].…”
Section: Introductionmentioning
confidence: 99%